MENDORONG KESIAPAN INDUSTRI 4.0: MENGEKSPLORASI SINERGI TRANSITIONAL LEADERSHIP, DYNAMIC CAPABILITIES, DAN ORGANIZATIONAL SUPPORT - Bahono, Afriza Ferdiansyah (DFAME Digital Financial Accounting Management Economics Journal, 2023)
This research investigates the realm of Industry 4.0 readiness within the Indonesian automotive manufacturing sector, exploring the intricate interplay between transitional leadership, dynamic capabilities, perceived organizational support, and organizational preparedness for the technological revolution. While the global presence of Industry 4.0 is undeniable, its implementation in Indonesia remains a challenge, prompting the investigation of the synergies between these constructs. The study employs a quantitative approach with cross-sectional data collected through questionnaires, focusing on multilevel positions within the industry. Results support four hypotheses, revealing positive relationships between transitional leadership and dynamic capabilities, transitional leadership and perceived organizational support, perceived organizational support and Industry 4.0 readiness, and dynamic capabilities and Industry 4.0 readiness. However, the correlation between transitional leadership and Industry 4.0 readiness is not substantiated. The study contributes to understanding the pivotal roles of dynamic capabilities and perceived organizational support in Industry 4.0 preparedness, underlining the significance of cohesive leadership and human resource development for successful technological transitions in the manufacturing sector.